Impacts of surface processes on west african climate - (:unkn) unknown (My University, 2005)
A 10-years simulation (1983-1992) of the west african climate is made using the regional climate model MAR, driven by the ECMWF reanalysis ERA-15. The validation mainly focuses on the analysis of the simulated rainy regime on various time scales (from daily to yearly). It is shown that MAR is able to simulate the main features of the west african rainy regime. Two defaults are identified : an underestimation of the simulated rainfall amounts over the sahelian area and a bad representation of the precipitation's daily structure. A comparison with daily rainfall data from IRD reveales the fact that the simulated rainfall is in agreement with observations for time scales larger than 3-5 days. The model's sensitivity to the prescription of surface's characteristics is also evaluated, through the simulation of the year 1992. Finally MAR is used in a process study in order to analyse the mecanisms acting in the unregular progression of the west african monsoon. An explanation is proposed, based upon thermal considerations and the spatial ditribution of albedo.
Keywords: African Research